Outcomes of Transferred Adult Venovenous and Venoarterial Extracorporeal Membrane Oxygenation Patients: A Single Center Experience - Zhao, Yang-Chao; Zhao, Xi; Fu, Guo-Wei; Huang, Ming-Jun; Zhao, Hui; Wang, Zhen-Qing; Li, Xing-Xing; Li, Jun (Frontiers in Medicine, 2022)
Objectives Extracorporeal membrane oxygenation (ECMO) patients with or without transport both have high hospital mortality rate and there are few data on adult VA-ECMO transport patients. Hence, this study was designed to analyze factors that affect the outcomes of patients with ECMO transport. Methods This study retrospectively enrolled 126 ECMO patients transferred from regional hospital to the First Affiliated Hospital of Zhengzhou University by our ECMO team during June 2012 to Sept 2020. Data were calculated and analyzed. Results The median distance of transportation was 141 (76–228) km, the median transport time consuming was 3 (1.3–4) h, the percentage of complications during transport was 40.5% (except for bleeding on cannula site, and no one death during transport), and the survival rate in hospital was 38.9%. Compared with survivors, the non-survivors were older and showed higher SOFA score, longer time with ECMO assisted, longer time in ICU and in hospital. However, after divided into VA-ECMO and VV-ECMO groups, the older age showed no significant difference between survivors and non-survivors groups of VA-ECMO patients. Moreover, the Cox regression survival analysis showed that higher SOFA score and lactate level indicated higher ICU mortality of VA-ECMO patients while higher SOFA score, higher lactate level, older age and lower MAP after transportation (<70mmHg) indicated higher ICU mortality of VV-ECMO patients. However, there was no significant difference of comorbidities and complications in survivors and non-survivors groups of ECMO patients. Conclusions The transportation for ECMO patients can be feasible performed although life-threatening complications might occur. The SOFA score and the lactate level could be used to evaluate the risk of ICU mortality of transportation ECMO patients. Besides, lower MAP after transportation (<70mmHg) had potential predictive value for short-term outcome of VV-ECMO patients.